Infecções oportunistas em portadores de HIV/AIDS da rede pública de Catanduva, Estado de São Paulo, Brasil - Schiesari Júnior, Arlindo (2010)
Hereby we present the epidemiological and clinical profile of the HIV-infected group before and during the HAART era from a tertiary care hospital catering to a large population from the Southeastern Brazilian region. A retrospective, cross-sectional and descriptive study was carried out, which involved the analysis of the medical records of patients diagnosed with HIV-1/AIDS admitted to Hospital Escola Emílio Carlos, located in the municipality of Catanduva, State of São Paulo, Brazil. In both pre-HAART and HAART periods, HIV-1 infection was more prevalent in men. Heterosexuality and secondary education were the risk facts for acquisition of the disease in the HAART period. Statistically significant association was only observed for co-infection with HIV-1/Hepatitis C in the pre-HAART era and the number of patients with opportunistic illness (OI) was lower in the HAART period. Among all these OI it is worth mentioning pulmonary pneumocystosis, since despite being frequent in the two periods, its occurrence was considerably greater in the pre-HAART era. Concerning the distribution of OI according to the HIV-1 viral load and serial count of T CD4+ lymphocytes, a significant association was observed. The association between the number of deaths by OI and the survival rate of less than 1 year in the HAART period was significant. The clinical and epidemiological picture of a specialized HIV-1/AIDS Center in a municipality in the southeastern region of Brazil is consistent with the current epidemiology of AIDS in the country. In conclusion, our results indicate that the OI are still important causes of morbi-mortality among HIV-1/AIDS infected patients in the municipality of Catanduva, particularly pulmonary pneumocystosis, tuberculosis and cryptococcal meningoencephalitis. We are aware that retrospective studies such as ours, which involve the review of patients’ medical records, may present some limitations arising from the scarcity or even absence of information.